Drivers and barriers to ICT sector development in the Gulf Cooperation Council: A policy-oriented analysis - Massalha, Mona (Asian Development Policy Review, 2025)
Information and communication technology (ICT) now underpins every primary diversification strategy in the Gulf region; however, the policy frameworks supporting it remain uneven. Drawing on qualitative content analysis of 68 national strategies, laws, and performance reports, supplemented by five multilateral briefs (2010–2024), this comparative study identifies the principal forces accelerating or hindering ICT development across the six Gulf Cooperation Council (GCC) states. It examines how government-led agendas, institutional designs, foreign direct investment, and human capital formation interact to shape nations’ digital trajectories. The study finds that state-driven innovation models have delivered world-class infrastructure: Qatar, for example, ranked third worldwide in the 2023 ICT Development Index. However, persistent skill shortages, institutional rigidity, and modest private-sector participation continue to constrain the sector’s long-term sustainability. By juxtaposing national reforms with international benchmarks, the study reveals convergences (e.g., aggressive 5G rollouts) and divergences (e.g., data governance regimes and depth of venture capital) in the GCC’s policy mix. These patterns are categorized into region-wide and country-specific policy paths that can facilitate a more resilient, innovation-led digital economy in the Gulf. The findings contribute to the broader debate on technological modernization in rentier states, helping identify the conditions wherein top-down investment can be reconciled with bottom-up innovation to secure sustainable, knowledge-based growth.